Menilik Nilai – Nilai Keislaman dalam Etika Profesi Personal Pengembang Teknologi Pembelajaran - Putra, Raffie Ahmad Riesman (Letiges, 2021)
Ethical aspects as a vital element in the study of Islamic education are not given much attention in learning by educators because of sudden disruption. This research aims to examine Islamic values ​​in the professional ethics of learning technology developers, as educators who are responsible for the ethical aspects of learning technology. The research method used is a document study to analyze various literature, especially government documents that regulate the professional ethics of learning technology developers. To be specific, the analysis is limited to the aspects of attitudes in the personal code of ethics: 1) honest, 2) creative and innovative, 3) professional, 4) collaborative, 5) independent, 6) lifelong learning, and 7) openness to change. The results show that each attitude contains various Islamic values. These values ​​are related to the exemplary attitude of the Prophet Muhammad, Islamic personality, the concept of Ijtihad, the implementation of Ta'awun, and the demand for knowledge that is relevant to Islamic law.